Benzo[d][1,2]thiazepin-5-one 3-Oxides: An Unexplored Scaffold with Anticancer Activity - Milokhov, Demyd S.; Pomalin, Mykhailo S.; Lutsiuk, Tetiana M.; Hys, Vasyl Y.; Virych, Pavlo A.; Poliudov, Anton O.; Popova, Maria V.; Shishkina, Svitlana V.; Volovenko, Yulian M.; Dobrydnev, Alexey V. (Synlett, 2025)
Herein, we report a simple and versatile method for the synthesis of previously unknown benzo[d][1,2]thiazepin-5-one 3-oxides through the CSIC (carbanion-mediated sulfonamide intramolecular cyclization) reaction strategy. The starting compounds are readily available methyl 2-(bromomethyl)benzoates and imino((di)methyl)((het)aryl)-λ6-sulfanones. The method works well with a wide range of substrates, proving its applicability for the synthesis of benzo- and heteroarene-fused derivatives. It allows for the effortless preparation of target endocyclic keto sulfoximines and easy scale-up without diminishing the yield. The synthetic utility of the target compounds was demonstrated by the preparation of several derivatives, some of them represented two novel heterocyclic systems. In vitro cytotoxicity assay showed selective cytotoxicity of S-phenyl-substituted benzo[d][1,2]thiazepin-5-one 3-oxide against triple-negative breast cancer cell line MDA-MB-231. The molecular docking study confirmed good binding affinity of both enantiomeric forms of endocyclic keto sulfoximines to the cancer-associated receptors, which are the therapeutic targets in cancer treatment.
Keywords: sulfoximines; CSIC reaction; cyclization; cytotoxicity; molecular docking